Implementation of the Cooperative Learning Model Type Problem Posing in Subjects Islamic Religious Education Lessons and Morals Towards Learning Independence And Critical Thinking Skills of Students of Senior High School 4 Kerinci - Ringgo Putra; Rehani Rehani; Rivdya Eliza (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
This study is motivated by the low levels of critical thinking and self-directed learning among the eleventh-grade students of SMA Negeri 4 Kerinci. In the process of learning Islamic Education (PAI) and Counseling Guidance (BP), students tend to be passive, with a lack of self-directed learning and insufficient critical thinking. Moreover, the problems discussed during lessons often relate to everyday life issues. The purpose of this research is to determine the improvement in self-directed learning and critical thinking skills among the students of SMA Negeri 4 Kerinci. The research employs a quasi-experimental design. The study variables include one independent variable: the Cooperative Learning Model with Problem Posing Type, and two dependent variables: self-directed learning and critical thinking. Data were collected using questionnaires and test questions. The population for this study consists of the eleventh-grade students of SMA Negeri 4 Kerinci enrolled in the 2023/2024 academic year. Sampling was conducted using random sampling techniques, resulting in Class XI IPA 3 as the experimental group and Class XI IPA 4 as the control group. Hypothesis testing was carried out to determine the significant effects of the applied strategy. The hypothesis test results for self-directed learning showed an average score of 88.3 for the experimental group and 77.1 for the control group. With a t-value of 5.15 and a t-table value of 1.708, it can be concluded that self-directed learning with the Cooperative Learning Model with Problem Posing Type is more effective than conventional teaching methods. The hypothesis test results for critical thinking skills showed an average score of 89.4 for the experimental group and 68.6 for the control group. With a t-value of 3.216 and a t-table value of 1.708, it can be concluded that critical thinking skills with the Cooperative Learning Model with Problem Posing Type are superior to those achieved through conventional teaching methods.